Práticas terapêuticas religiosas no tratamento da drogadicção : estudo de caso na comunidade Desafio Jovem de Sergipe - Dórea, Adalgisa Viana (2011)
Since the second half of the last century the therapeutic communities that employ religion to treat chemical addicted have been spreading all over the world and statabilishing them-selves as a therapeutic alternative. The proposition of this communities is based on reception, complete abstinence from any psychoactive substance, occupational therapy, group therapy (Monitored by a psychologist or not) and mainly religious therapy and its set of ethic, spiritual and subjective principles in order to promote recovery by employing a new approach religion. The research universe of this work is the Comunidade Terapêutica Desafio Jovem de Sergipe. Withen this empiric universe aims to reporter the therapeutic itinerary, the profile of the community and their available assistance, and the possible practices employed on the recovery of addicted people. This research intends to demonstrate through the narrative of the therapists and chemical addicted in recovery, their notion of disease, health and religion in order to comprehend the process that involves the employment of religious practices on the treatment of the chemical addicted, within the symbolic universe that involves the therapeutic practices. So, this dissertation intended to be a practical exercise of the sociological, anthropological and religious studies on the disease as well as a source of information about the management of religious therapy for chemical addicted.